2005
DOI: 10.1002/hep.20766
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory function and hepatorenal syndrome in cirrhosis†

Abstract: The pathogenic mechanism of hepatorenal syndrome is not well established. We investigated the circulatory function in cirrhosis before and after the development of hepatorenal syndrome. Systemic and hepatic hemodynamics and the activity of endogenous vasoactive systems were measured in 66 patients who had cirrhosis with tense ascites and normal serum creatinine levels; measurements were repeated at follow-up in 27 cases in whom hepatorenal syndrome had developed. At baseline, mean arterial pressure and cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
365
4
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(389 citation statements)
references
References 23 publications
11
365
4
9
Order By: Relevance
“…In the present study there was no statistically significant change in renal parameters in different aetiologies of liver disease but the result was different in other studies [18][19][20] like prevalence rate of AKI in cirrhosis was 68% in a study conducted by Fernandez-Seara J [18] but in our study only 10% patients had AKI. In the same study prevalence of hepatorenal syndrome was 25% [18].…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…In the present study there was no statistically significant change in renal parameters in different aetiologies of liver disease but the result was different in other studies [18][19][20] like prevalence rate of AKI in cirrhosis was 68% in a study conducted by Fernandez-Seara J [18] but in our study only 10% patients had AKI. In the same study prevalence of hepatorenal syndrome was 25% [18].…”
Section: Resultscontrasting
confidence: 98%
“…In the same study prevalence of hepatorenal syndrome was 25% [18]. Another study showed that among patients with ascites, HRS developed in about 20% and 40% of the patients, at 1 and 5 years, respectively [19]. Ruiz-del-Arbol L et al, [20] in a study done on 23 cirrhotic patients with spontaneous Bacterial peritonitis of which 8 patients developed type-I Hepatorenal syndrome.…”
Section: Resultsmentioning
confidence: 82%
“…The same group studied the systemic and hepatic hemodynamics of 66 patients with cirrhosis and tense ascites and normal serum creatinine at baseline with repeat measurement in 27 patients who subsequently developed HRS. At baseline, arterial BP and CO was significantly lower whereas RAAS and SNS activity were significantly higher in the group that developed HRS with further reduction in CO at the onset of renal dysfunction (43). The findings of these two studies suggest that a decrease in CO identifies a group of patients who are at risk for HRS and implicate decreased CO or its cause in HRS occurrence.…”
Section: Cardiac Dysfunctionmentioning
confidence: 78%
“…Indeed, in cirrhotic patients with spontaneous bacterial peritonitis, patients who went on to develop hepatorenal syndrome (HRS) had a reduced cardiac output at infection diagnosis, which decreased further at infection resolution [79], suggesting that the inability to mount a sufficient cardiac output in the presence of bacterial infection has contributed to a reduced renal perfusion pressure, thereby contributing to the development of HRS. In fact, the same authors reported that those cirrhotic patients destined to develop HRS had lower cardiac output even prior to the onset of HRS [80], with lower mean arterial pressure and higher neurohormonal levels, suggesting that an inadequate cardiac output in the presence of systemic arterial vasodilatation predisposes these cirrhotic patients to further complications. In the case of bacterial infections, the presence of negative inotropic cytokines such as TNF-a and interleukin-1b further lowers cardiac systolic function, thereby further reducing cardiac output, leading to the development of HRS.…”
Section: Clinical Presentations and Consequences Of Cirrhotic Cardiommentioning
confidence: 98%